TATA KELOLA TAMAN HUTAN KELONO SEWANDONO KABUPATEN PONOROGO - Surojo, Amor; Hilman, Yusuf (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kota Samarinda, 2024)
This study aims to describe and analyze the governance of Kelono Sewandono Forest Park in Ponorogo Regency using the theory of Good Environmental Governance. According to this theory, good environmental management involves the roles of all stakeholders, including the government, NGOs, the private sector, and civil society, to achieve environmental sustainability. The research methodology used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The research results show that the park management has followed existing regulatory principles; however, there are still obstacles such as budget constraints and vandalism. Efforts to increase public understanding of park rules and active participation from various stakeholders, including CSR involvement from the private sector, are expected to improve the park's management effectiveness. A systematic and collaborative approach between the government and the community is needed to create a clean, safe, and sustainable park.